Obstructive Sleep Apnea Syndrome (OSAS): Who Are Our Patients? - Natália Silva Cavalcanti (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
The Obstructive Sleep Apnea Syndrome (OSAS) is characterized by interruption or reduction of airfl ow during sleep despite respiratory effort, causing awakenings, oxyhemoglobin desaturation and excessive daytime sleepiness. It is considered a serious public health problem, according to recent national surveys prevalence up to 30% of the general population, reaching alarming levels [1,2]. OSAS can be undiagnosed in 80% of cases [3].